Efficacy of Systemic Single-dose Diclofenac, Tramadol, and Placebo Immediately after Caesarean Section under Intrathecal Morphine - Kham-im, Kriangsak; Choojai, Meena; Luangareeporn, Sudarat (Journal of Health Science of Thailand, 2018)
Postoperative pain relief after caesarean section delivery under spinal anesthesia can be effectively obtained by intrathecal morphine but its dose-dependent side effects are well recognized. Any techniques that could potentiate the analgesic effects and reduce its unsatisfactory property are of interest. This study was a prospective randomized controlled trial. One hundred fifteen parturients scheduled for elective caesarean section under spinal anesthesia using 0.5% hyperbaric bupivacaine combined 0.2 mg intrathecal morphine were allocated into three groups, each receiving single dose intramuscular diclofenac 75 mg, tramadol 50 mg, or placebo immediately after caesarean section. The aim of this study was to compare the pain-control efficacy of analgesia post operation in the three groups. Mean visual analogue scores of postoperative pain diclofenac was significantly lower than that of placebo at 3-hour postoperative period and significantly lower than tramadol at 3 and 6-hour postoperative periods. Adverse effects including nausea/vomiting, pruritus, and sedation were not different among the three groups. In conclusion, combination of low dose intrathecal morphine with single-dose intramuscular diclofenac immediately post caesarean section provided better pain control in addition to attenuation of high-dose intrathecal morphine side effects. These benefits would result in early ambulation, comfort, and the ability to care newborns of the patients.